Barrier Lyapunov function based adaptive finite-time control for hypersonic flight vehicles with state constraints. (January 2020) - Dong, Chaoyang; Liu, Yang; Wang, Qing
Abstract: This paper investigates the finite-time tracking control problem of the hypersonic flight vehicle (HFV) with state constraints. Firstly, a control-oriented model is introduced to enable the application of adaptive backstepping scheme. To meet strict requirements in terms of working conditions of HFV, barrier Lyapunov function is adopted to constrain the tracking errors, while piecewise saturation function is constructed to restrict the virtual signals. To guarantee the finite-time convergent property of HFV dynamics, an adaptive scheme in accordance with finite-time stability theory is designed. Meanwhile, a sliding mode differentiator is employed to estimate the derivatives of the virtual control laws. Novel auxiliary systems are then designed to consider the side effects of the possible saturation and to maintain the finite-time convergent property. In the final stage, the effectiveness and performance of the proposed method is demonstrated by numerical simulations. Highlights: Barrier Lyapunov function is combined with the theory of finite-time stability. State constraints are guaranteed by restricting magnitudes of virtual controls and employing barrier Lyapunov function design. Auxiliary systems in accordance with barrier Lyapunov functions are designed to contribute to the finite-time convergent property of the closed-loop system. Compared with existing BLF based designs for HFV, the proposed scheme relaxes the requirements on initial conditions.